KEGIATAN MEDIA RELATIONS FAVEHOTEL SEBAGAI UPAYA PUBLIKASI DI MEDIA MASSA - Dr. Dian Esti N, M.Si, Dra. Nurnawati H.H, M.Si, Tri Pujowati, (Solidaritas, 2018)
ABSTRACTÂ Frank Jefkins says media relations is an attempt to reach publications to inform activities about his company. Media relations is shown by Favehotel Solos public relations activities in the form of press release, press conference (press conference), and on radio talkshow (radio broadcast). The purpose of this study provides the understanding that good and interesting writing will help in the process of preparing the news by the mass media who do coverage. In addition, a personally built relationship will also help, such as the relationship between public relations practitioners and journalists. News coverage in the mass media is not just in print and online media, electronic media such as radio is also influential, when seeing most of the local community still believe the voice of broadcasters and radio stations can provide its own stimulants. This research uses qualitative descriptive. Informants are public relations, journalists / journalists, sales and marketing departments, visitors. Research results menunujukkan, public relations professionalism or public relations in packaging information or activities in writing press releases and build relationships with the mass media is very helpful in obtaining a place of news, so as to obtain positive public opinion.Kata Kunci : Public Relations, Media Relations, Press Release, Radio